2006
DOI: 10.1016/j.ygyno.2006.03.045
|View full text |Cite
|
Sign up to set email alerts
|

hMLH1 promoter methylation and silencing in primary endometrial cancers are associated with specific alterations in MBDs occupancy and histone modifications

Abstract: Objective-To investigate the relationship between hMLH1 promoter methylation and changes in chromatin composition. To study how the occupancy of methyl CpG binding domain proteins (MBDs) and histone acetylation/methylation in hMLH1 promoter may participate in hMLH1 silencing.Methods-64 endometrial cancer samples were screened for hMLH1 mRNA expression. hMLH1 promoter methylation status was confirmed by methylation-specific PCR in cancers with high and low levels of hMLH1 expression. Chromatin immunoprecipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Here we analyzed the changes of H3K9me2 and H3K4me3 occupancy at the MLH1 promoter during chromate-induced silencing of the active MLH1 gene which differs from studies that re-activated silenced MLH1 gene in cancer cells. Our findings demonstrate that the enrichment of H3K9me2 at MLH1 promoter is highly correlated with MLH1 gene inactivation supporting the previous reports that H3K9me2 is important for both initiation and maintenance of gene silencing (McGarvey et al, 2006; Xiong et al, 2006). We do not know whether acute exposure of chromate is able to induce DNA hypermethylation in MLH1 promoter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here we analyzed the changes of H3K9me2 and H3K4me3 occupancy at the MLH1 promoter during chromate-induced silencing of the active MLH1 gene which differs from studies that re-activated silenced MLH1 gene in cancer cells. Our findings demonstrate that the enrichment of H3K9me2 at MLH1 promoter is highly correlated with MLH1 gene inactivation supporting the previous reports that H3K9me2 is important for both initiation and maintenance of gene silencing (McGarvey et al, 2006; Xiong et al, 2006). We do not know whether acute exposure of chromate is able to induce DNA hypermethylation in MLH1 promoter.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, other factors including histone modification (McGarvey et al , 2006; Xiong et al , 2006; Meng et al , 2007) and nucleosome occupancy (Lin et al, 2007) at the promoter region have been implicated in the regulation of MLH1 gene expression. Enrichment of the repressive histone marks, H3K9me1, H3K9me2, H3K9me3, H3K27me2, and H3K27me3 were found at the hypermethylated MLH1 promoter in MLH1 silenced cells compared with the unmethylated active promoter in MLH1 expressing cells (McGarvey et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the methyl DNA binding proteins, MDB2 and MeCP2, bind not just to densely methylated re- on May 10, 2018 by guest http://mcb.asm.org/ gions of DNA but also to isolated methyl CpG dinucleotides (45,54). Hence, we also tested by ChIP for the presence of MDB2 and MeCP2 at the BRCA1 promoters in MCF-7 cells exposed to hypoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the generation of two MDR-independent, vorinostat-resistant sublines [12]: these were the DNA mismatch repair (MMR)-proficient HCT116ch3 colorectal adenocarcinoma cell line (supplemented with chromosome 3 harboring the wildtype copy of the MLH1 gene to compensate for the MLH1 gene truncating mutation present in the parental MMRdeficient HCT116 cell line) and the MMR-deficient HCT116ch2 cell line (supplemented with the MLH1-irrelevant chromosome 2 for chromosome balance). Although a relationship between MLH1 expression and histone acetylation has been suggested [13,14], this vorinostat-induced resistance was independent of the presence or absence of MLH1 protein. Noteworthy, these vorinostat-resistant sublines were cross-resistant to the HDAC inhibitor trichostatin A but retained sensitivity to non-HDAC inhibitor-type anticancer agents.…”
Section: Introductionmentioning
confidence: 87%